Paraneoplastic cerebellar degeneration in platinum-responsive endometrial cancer: A case report and review of literature - Michalis Liontos; Oraianthi Fiste; Danai Drakopoulou; Nikolaos Thomakos; Kalliroi Goula; Flora Zagouri; Maria Anagnostouli; Meletios-Athanasios Dimopoulos (Elsevier, 2021)
Paraneoplastic cerebellar ataxia is a rare immune-induced, non-metastatic neurologic syndrome, most frequently associated with gynecological cancers, which carries an abysmal prognosis. We report the case of a patient with advanced-stage uterine cancer, who developed severe pancerebellar ataxia, while in partial remission, after the completion of 3 cycles of neoadjuvant platinum-based chemotherapy. Swift initiation of immunosuppressive therapy with corticosteroids combined with plasmapheresis did not result in significant clinical benefit. Early recognition of this debilitating condition and standardization of its treatment strategy are prerequisites for both improved survival outcomes and quality of life in these patients. Further studies are warranted to clarify the immune-stimulating impact of effective cytotoxic chemotherapy and the occurence of autoimmune paraneoplastic neurological syndromes.